2019
DOI: 10.1177/2054358119841611
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Risk-Based Care for Patients With Chronic Kidney Disease in the Community: Study Protocol for a Cluster Randomized Trial

Abstract: Background: A risk-based model of care for managing patients with chronic kidney disease (CKD) using the Kidney Failure Risk Equation (KFRE) has been successfully integrated into nephrology care pathways in several jurisdictions. However, as most patients with CKD can be managed in primary care, the next pertinent steps would be to integrate the KFRE into primary care pathways. Objective: Using a risk-based approach for guiding CKD care in the primary care setting, the objective of the study is to develop, imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…In some Canadian provinces, a risk threshold of >3% is being used in current clinical practice and this is being evaluated in improvement programs. 11 , 12 , 13 A further weakness of the study included the exclusion of patients with an eGFR of ≥60 ml/min per 1.73 m 2 and abnormal urinalysis. However, only young patients with nephrotic range proteinuria (ACR >300 mg/mmol) and an eGFR ≥60 ml/min per 1.73 m 2 will have a risk of progression to ESRD of >3% at 5 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some Canadian provinces, a risk threshold of >3% is being used in current clinical practice and this is being evaluated in improvement programs. 11 , 12 , 13 A further weakness of the study included the exclusion of patients with an eGFR of ≥60 ml/min per 1.73 m 2 and abnormal urinalysis. However, only young patients with nephrotic range proteinuria (ACR >300 mg/mmol) and an eGFR ≥60 ml/min per 1.73 m 2 will have a risk of progression to ESRD of >3% at 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…CKD populations globally have contributed to this model’s extensive external validation, 9 including CKD cohorts within the United Kingdom, 9 , 10 and it is being evaluated in improvement programs in Canada. 11 , 12 , 13 The equation can easily be imbedded into electronic medical records where patients’ clinical and laboratory data can be incorporated and it is also readily available online. 14 There may be scope to improve the accuracy of the equation and studies have investigated the addition of other variables 15 , 16 , 17 , 18 , 19 , 20 or recalibrated to local populations, 10 and have also explored broadening its use by validating certain populations such as renal transplant recipients 21 , 22 and children.…”
mentioning
confidence: 99%
“…A study designed to assess the clinical impact of KFRE implementation in a primary care CKD study cohort in the United Kingdom, found that application of a KFRE-based cutoff of greater than 5% 5year risk expands eligibility for nephrology referral compared to existing guidelines [12]. An ongoing multicenter cluster randomized controlled trial plans to assess the impact of a risk-based care approach on management of CKD, including use of ACE-I/ARBs, sodium-glucose cotransporter 2 inhibitors, hypertension management, and cardiovascular risk mitigation [14].…”
Section: Discussionmentioning
confidence: 99%
“…The KFRE has been studied in the context of risk-based triage for nephrology referrals in order to optimize health system capacity, and proposals for primary care adoption of CKD risk-stratification have been published [11][12][13][14]. Importantly, it has been recognized that albuminuria measurement represents a limitation to risk-based approaches, given historically low rates of completion of this test [15].…”
Section: Introductionmentioning
confidence: 99%
“…A trial aimed at determining if KRFE risk-based approach improves CKD management in the primary care pathways is in progress. 28 Rapid progression is defined as a sustained declined in eGFR of > 5 mL/min/1.73m 2 per year. These patients are at an increased risk of rapid progression to ESKD and also an increased risk of death and vascular disease-related events 7 and will benefit from consulting a Nephrologist.…”
Section: Which Ckd Patients Do Worse?mentioning
confidence: 99%